Pleurocarpous mosses of Bangladesh : Family Entodontaceae - Khatun, Hamida; Hadiuzzaman, Syed (Bangladesh Journal of Plant Taxonomy, 2006)
Three species, namely, Erythrodontium julaceum, Pterigynandrum decolor and Entodon flavescens under family Entodontaceae are described with illustrations and a short note on each. Key words: Pleurocarpous mosses, Hypnobryales, Entodontaceae, Bangladesh DOI: 10.3329/bjpt.v13i2.584 Bangladesh J. Plant Taxon. 13(2): 131-137, 2006 (December)